The Role of Perceived Social Support in Enhancing Psychological Well-Being among Pesantren Teachers - Khodir, Abdul; Dewi, Damajanti Kusuma; Khoirunnisa, Riza Noviana (International Journal of Islamic Educational Psychology, 2026)
Educators in Indonesian Islamic Boarding Schools operate under a complex triple mandate that requires them to act simultaneously as academic instructors, moral guides, and character builders. The complexity of these overlapping roles, combined with the constant expectation to serve as flawless moral exemplars within a highly communal environment, creates a unique psychological vulnerability among these educators. Therefore, this study aims to determine and analyze the predictive influence of perceived social support on teachers' psychological well-being across four schools within Islamic Boarding School X in Bojonegoro, East Java, Indonesia. A quantitative cross-sectional design was employed, using a saturated sampling technique to capture data from all 264 teachers across various educational tiers. Data were collected via highly validated psychological well-being and multidimensional perceived social support scales, and subsequently analyzed using simple linear regression. The results demonstrated that perceived social support significantly predicted teachers' psychological well-being (β = .534, t = 10.227), explaining 28.5% of the variance (R² = .285). These findings indicate that higher levels of perceived social support are associated with better psychological well-being among pesantren teachers. The study highlights the importance of strengthening social support systems within Islamic boarding schools to promote teachers' psychological well-being and support their professional functioning. The originality of this study lies in extending the literature on psychological well-being by examining the predictive role of perceived social support among pesantren teachers within the distinctive context of Indonesian Islamic boarding schools.